2006
DOI: 10.1111/j.1556-4029.2006.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Alcohol‐Induced Blackouts and Grayouts to Blood Alcohol Concentrations

Abstract: The primary aim of this study was to investigate the association between measured blood alcohol concentration (BAC) and the presence and degree of amnesia (no amnesia, grayout, or blackout) in actively drinking subjects. A secondary aim was to determine potential factors other than BAC that contribute to the alcohol-induced memory loss. An interview questionnaire was administered to subjects regarding a recent alcohol associated arrest with a documented BAC greater than 0.08 g/dL for either public intoxication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 13 publications
2
60
1
3
Order By: Relevance
“…Drinkers seeking alcohol's positively reinforcing effects (i.e., those reporting enhancement motives) may not simply drink in larger overall quantities, but may drink faster or in larger sips, a style of drinking that may place them at greater risk for blackouts (Goodwin, 1995;Goodwin et al, 1969;Perry et al, 2006). The increased risk for social/ interpersonal problems among those reporting higher enhancement motives may be a result of the contexts in which enhancement-motivated drinking takes place.…”
Section: Enhancement Motivesmentioning
confidence: 98%
“…Drinkers seeking alcohol's positively reinforcing effects (i.e., those reporting enhancement motives) may not simply drink in larger overall quantities, but may drink faster or in larger sips, a style of drinking that may place them at greater risk for blackouts (Goodwin, 1995;Goodwin et al, 1969;Perry et al, 2006). The increased risk for social/ interpersonal problems among those reporting higher enhancement motives may be a result of the contexts in which enhancement-motivated drinking takes place.…”
Section: Enhancement Motivesmentioning
confidence: 98%
“…Behavioral measures such as number of blackouts may be indicators of rapid alcohol consumption (ie, gulping rather than drinking more steadily and slowly), which may in part reflect poor impulse control (Goodwin, 1995;Perry et al, 2006). Previous work has also demonstrated increased frontocerebellar response to a Go/No-Go task in substancenaive youth who later experience alcohol-related blackouts, suggesting pre-existing abnormalities in inhibitory processing that underlie blackout propensity (Wetherill et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, alcohol-induced blackouts have been reported by roughly half of college drinkers (White et al, 2002) and are commonly seen with a quick rise in BAC as the result of rapid, excessive intake of alcohol (Perry et al, 2006;Ryback, 1970). Indeed, studies have repeatedly shown that blackouts are a consequence of heavy drinking in college students (Barnett et al, 2014;Read et al, 2008).…”
Section: Blackouts and Alcohol Dependencementioning
confidence: 99%